Quality of urban settlements around the University of Jenderal Soedirman (unsoed) Purwokerto - Puspaningrani, F.C. (Institute of Physics, 2022)
This study aims to determine the quality conditions of settlements in Karangwangkal Village. The study conducted using a quota sampling technique with a total sample of 210 household heads. Quality of settlement data obtained from observations and interviews with respondents were processed using a scoring method and classified using Sturges rule into classes of settlement quality, namely low, medium, and high. The analysis used is quantitative descriptive and presented in the form of a single frequency table and pie diagrams to determine the quality conditions of settlements in Karangwangkal. The results showed that the research area was medium-quality settlements dominated (47). This study also found that the smaller distance between settlements and campus, the higher the quality of settlements. © Published under licence by IOP Publishing Ltd.